A Comparative Study of Marlowś Play Dr. Faustus and Quranic Verses - Salwa Abdulamir Had; Saad Laftah Shamkhi; Basim Jubair Kadhim (RIRAI Publisher, 2023)
In this research, we examine environmental education in the context of Moroccan secondary schools, focusing on the field of physics teaching. Our investigation is based on an analysis of empirical observations provided by physics teachers. To this end, a structured questionnaire was administered to 120 physics teachers from various high schools located in the academic area of Fez-Meknes in Morocco. The results clearly underline the importance of assimilating environmental education principles in the teaching of physics. This environmental education clearly favors the cultivation of students' inclination and disposition towards the subject. In addition, the questionnaire data also provide enlightening indications in favor of integrating environmental education paradigms into the didactic apparatus of physics-related knowledge in secondary education. This integration promises to develop sustainable skills in students, galvanizing their capacity to adopt environmentally friendly behaviors.